Importance of the actual plant height in modulating the within-community spectrum of plant form and function - He, Dong; Yan, En-Rong; Zheng, Li-Ting; Song, Yan-Jun; Yang, Xiao-Dong; You, Wen-Hui; Cornelissen, J. Hans C. (Frontiers in Plant Science, 2025)
Maximum height (Hmax) is a principal driver or correlate of interspecific variation in many plant functional traits. Still, it remains unclear why leaf resource economic traits are invariant with Hmax at global scale and why broad-scale interspecific trait correlations are not retained at local scale. Here we proposed that the actual plant height (Hact), which is tightly linked with highly localized abiotic and biotic interactions, is more important than Hmax in determining plant morpho-physiological traits among locally co-occurring plants. We tested the idea across community, regional, and global scales. We also examined correlations among 22 traits, including leaf physiology, hydraulics, and crown architecture, within a subtropical forest in Eastern China. Additionally, we explored how Hact-driven trait variations align with vertical patterns of microclimates. Results showed stronger correlations between leaf traits and Hact at the community level, except for leaf area. Intraspecific variation exceeded interspecific variation, and trait correlations were stronger at the individual level than at the species level. Hact positively correlated with traits like crown area, leaf mass per area, stomatal density, and hydraulic conductivity but negatively with stem hydraulic safety margin and leaf coverage. Vertical changes in photosynthetically active radiation explained most Hact-driven trait variations. Our findings suggest that Hact influences plant trade-offs in biomass allocation and photosynthetic-hydraulic limitations, shaping functional diversity within communities. This highlights Hact as a key factor in balancing resource use, support, and water transport among coexisting plants.